Gut feelings: the microbiota-gut-brain axis on steroids - So, Sik Yu; Savidge, Tor C. (American journal of physiology: Gastrointestinal and liver physiology, 2022)
The intricate connection between central and enteric nervous systems is well established with emerging evidence linking gut microbiota function as a significant new contributor to gut-brain axis signaling. Several microbial signals contribute to altered gut-brain communications, with steroids representing an important biological class that impacts central and enteric nervous system function. Neuroactive steroids contribute pathologically to neurological disorders, including dementia and depression, by modulating the activity of neuroreceptors. However, limited information is available on the influence of neuroactive steroids on the enteric nervous system and gastrointestinal function. In this review, we outline how steroids can modulate enteric nervous system function by focusing on their influence on different receptors that are present in the intestine in health and disease. We also highlight the potential role of the gut microbiota in modulating neuroactive steroid signaling along the gut-brain axis.